Memoria y presente en el relato periodístico (2013)
This analysis stresses how the press doubles in its professional role of an- swering, “what’s happening” while enabling the individual to use the so- cial substance of the present. In this endeavor, it is paramount to stress the importance of consolidating a method of inquiry of surrounding reality that is similar to that of other social fields and to apply that method to per- manently recall the past in order to interpret current events in accordance with past events. In the end, this task is brought together in clearly defined informational products or reports that stress the importance of perceiving journalism not only for the work as such but for what it stands for and what it means to contemporary society.